ANALISIS RENCANA BISNIS PADA STARTUP NOMINUS - -, Danendra Erico Rafifata Tiyasa; -, Imanuddin Hasbi (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to analyze the business plan and strategy of each part of the company from NoMinus startup, a platform that focuses on selling fashion and pre-loved products. The analysis of startup NoMinus uses various analysis methods, one of which is Strength Weakness Opportunity Threat (S.W.O.T) and Business Model Canvas (B.M.C). The data used in this research was collected through online surveys, and various sources of information that have been published previously. The results of the SWOT analysis show that NoMinus has strengths in business model and marketing strategy, but faces weaknesses in limited budget, lack of team members, and dependence on vendor or seller cooperation. Opportunities in the growing fashion e-commerce market are factors that support the growth of this business. On the other hand, the threat of intense competition is a challenge that must be faced. Therefore, the proposed strategic plan, which includes increasing the number of team members, developing partnerships with various vendors, and adjusting transaction rates to break even faster, are important steps to support NoMinus' business operations and expansion.